2013
DOI: 10.1177/1461445613483038
|View full text |Cite
|
Sign up to set email alerts
|

Managing troubles-talk in the renegotiation of a loan contract

Abstract: This study focuses on troubles-tellings in calls to the Swedish Board for Student Support, where the caller wants to negotiate the repayment contract of a student loan. The study relates to research on the organization of troubles-tellings in institutional interaction, and the overall question of how talk about money is a delicate matter that is shaped by moral concerns. The data consist of 94 calls in which the caller proposes either a reduction or a temporal suspension of repayment. The analysis shows that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
1
23
0
Order By: Relevance
“…A common response to callers' complaints in this context of the calls is the combination of acknowledgments and the projection of a shift towards the main reason for call (the caller's responsibility for initiating the reason for call, and its distinct character in this institutional context, are analyzed in Ekström et al, 2013). The complaints are recognized without being engaged with or contributed to (cf.…”
Section: Shift Devicesmentioning
confidence: 99%
“…A common response to callers' complaints in this context of the calls is the combination of acknowledgments and the projection of a shift towards the main reason for call (the caller's responsibility for initiating the reason for call, and its distinct character in this institutional context, are analyzed in Ekström et al, 2013). The complaints are recognized without being engaged with or contributed to (cf.…”
Section: Shift Devicesmentioning
confidence: 99%
“…Institutional advice‐giving is also asymmetric: medical consultations between physicians and patients are examples of institutional talk where one participant is established as the ‘expert’ in comparison with the other through interaction (Heritage, ; Maynard, ; Peräkylä, ). CA and DP have been used in research on a range of institutional advice contexts, including helplines (Butler, Potter, Danby, Emmison, & Hepburn, ; Emmison, Butler, & Danby, ; Hepburn, ; Potter & Hepburn, ), police interviews (Stokoe & Edwards, ), conversations between health visitors and first‐time mothers (Heritage & Lindström, ; Heritage & Sefi, ), pharmacists and patients (Pilnick, ), peer tutoring (Waring, , ), and renegotiation of student loans (Ekström et al ., ). However, although Ekström et al .…”
Section: Introductionmentioning
confidence: 97%
“…In a rare example of research on debt advice conversations, Ekström, Lindström, and Karlsson () found that talking about money is a delicate concern and that debtors presented themselves as responsible characters when organizing their ‘trouble‐tellings’. For example, callers made an effort to produce an account for why they were renegotiating their payment loans.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations